Willingness to pay for shrimp attributes and evidence of stigma following the Gulf Coast oil spill. Issue 1 (2nd January 2016) - Ellis, Addison; Kropp, Jaclyn; Norton, Michael
ABSTRACT: Mandatory labeling requirements in the United States require shrimp products to be labelled with certain credence attributes: production process and country of origin. To determine the effects of these requirements in the wake of the 2010 Gulf Coast oil spill, we estimate willingness to pay (WTP) for various credence characteristics (geographic origin and production process) and physical attributes using a Becker DeGroot Marschak experimental auction. Although the results are obtained from a small convenience sample, and hence cannot be generalized, we find that participants are willing to pay premiums of $0.90–$1.23 per half-pound for domestic shrimp (regardless of production method) and $0.60–$1.03 per half-pound for wild-caught shrimp. We also find evidence that Gulf Coast shrimp are stigmatized; controlling for other characteristics, participants are willing to pay $1.03–$1.34 less per half-pound for Gulf Coast shrimp. Overall, credence attributes influence WTP more than physical attributes.